The Impact of Affiliate Marketing and Service Features on E-Commerce Consumers Buying Interest - Lindi Utami Marquerette; Syifa Fauziah Hamidah (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The development of information technology in the 4.0 era has made business people make many changes in their business strategy, affiliate marketing is one of the marketing strategies that is being widely used today, apart from that, service features in the digital world are elements that need attention in influencing consumer buying interest. The purpose of this study is to find out how affiliate marketing, service features, and buying interest consumers of TikTok Shop e-commerce. And to find out how much impact affiliate marketing has on buying interest, the impact of service features on buying interest, as well as the influence of affiliate marketing and service features on buying interest. In this study, the independent variable (X) is affiliate marketing and service features, and then the dependent variable (Y) is buying interest consumers. This research is a sample study where consumers are respondents to this study, for data collection using a questionnaire with a total of 100 respondents. The analytical method used is a quantitative method with descriptive analysis. To process the data, the author used Microsoft Excel 2019 and SPSS 26 For Windows. The result of this study is either partially or simultaneously affiliate marketing and service features have a positive effect on e-commerce consumers buying interest.